1992
DOI: 10.1111/j.1365-3040.1992.tb01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium — citric acid — xylem cell wall interactions in tomato plants

Abstract: Mutual interactions between cadmium ions, citric acid and xylem cell walls were examined. Cadmium and citric acid were measured as "^Cd and [1,5-^*'C] citric acid, respectively. Xylem cell walls were obtained by bacterial degradation of tomato stem sections {Lycopersicon esculentum Mill, cv. Tiny Tim), and applied as ion-exchange columns. The xylem column material carried 2 4dm3 HzO kg "^ dry weight, and was temporarily capable of buffering perfusates at pH 5 7, Sorbed cadmium and citric acid were determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 51 publications
1
25
1
Order By: Relevance
“…The efficiency of metals transfer in the xylem in the form of a complex with organic acids is attributed to the lower adsorption of uncharged or negatively charged chelated forms of metals by the negatively charged cell walls of xylem, as well as to a decrease in lateral removal of metals from the vessel, which was noted in particular for Zn and Cd (Senden, van Paassen, Van der Meer, and Wolterbeek, 1992). The role of organic acids in the intracellular detoxification of metals has been studied most intensively in heavy metal hyperaccumulators (Rauser, 1999;Küpper, Mijovilovich, Meyer-Klaucke, and Kroneck, 2004;Sun, Zhou, and Jin, 2006;Yang et al, 2006), and primarily for Zn/Cd hyperaccumulators Thlaspi caerulescens and Arabidopsis halleri (Cosio, Martinoia, and Keller, 2004).…”
Section: The Involvement Of Organic Acids In Transport and Internal Cmentioning
confidence: 99%
“…The efficiency of metals transfer in the xylem in the form of a complex with organic acids is attributed to the lower adsorption of uncharged or negatively charged chelated forms of metals by the negatively charged cell walls of xylem, as well as to a decrease in lateral removal of metals from the vessel, which was noted in particular for Zn and Cd (Senden, van Paassen, Van der Meer, and Wolterbeek, 1992). The role of organic acids in the intracellular detoxification of metals has been studied most intensively in heavy metal hyperaccumulators (Rauser, 1999;Küpper, Mijovilovich, Meyer-Klaucke, and Kroneck, 2004;Sun, Zhou, and Jin, 2006;Yang et al, 2006), and primarily for Zn/Cd hyperaccumulators Thlaspi caerulescens and Arabidopsis halleri (Cosio, Martinoia, and Keller, 2004).…”
Section: The Involvement Of Organic Acids In Transport and Internal Cmentioning
confidence: 99%
“…In previous experiments with plant sub-systems (Senden and Wolterbeek, 1990;Senden et al, 1992a), effects of citrate on Cd xylem transport characteristics were observed. The present experiments were performed to get more insight in the effects of citric acid on Cd accumulation and mobility in whole plants.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Tsukamoto et al (2006) reported that the velocity of transport of 52 Mn in the shoot from the shoot base was 3.6 cm h 21 in a 3-week-old manganesedeficient barley plant, which was very similar to our results with Cd. It is known that interactions take place between cationic solutes and negatively charged groups in the cell walls of the xylem vessels along the pathway from the roots to the leaves (Marschner, 1995), and organic chelating compounds including citrate affect these interactions (Senden et al, 1992). We speculated that Cd (and probably manganese as well) bound to organic compounds in the xylem flow interacts with the cell walls of the xylem vessels, and this makes the transport velocity slower than that of the bulk flow, for which the mechanism is similar to chromatography.…”
mentioning
confidence: 99%